2015
DOI: 10.1245/s10434-014-4333-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reduced Port Totally Laparoscopic Distal Gastrectomy (Duet TLDG) and Conventional Laparoscopic-Assisted Distal Gastrectomy

Abstract: Reduced port duet TLDG for early gastric cancer is feasible in terms of patient safety and quality of lymph node dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 19 publications
5
29
0
Order By: Relevance
“…In this study, the operative time was statistically shorter in TP-LDG group compared to that in FP-LDG group, similar to the result of previous studies comparing various types of RPLG and FP-LDG [15,16]. The operative time is influenced by many factors, such as operator's proficiency, BMI, previous abdominal surgery history, anatomical characteristics, bleeding risk, tumor characteristics, extent of LNs dissection and reconstruction method.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, the operative time was statistically shorter in TP-LDG group compared to that in FP-LDG group, similar to the result of previous studies comparing various types of RPLG and FP-LDG [15,16]. The operative time is influenced by many factors, such as operator's proficiency, BMI, previous abdominal surgery history, anatomical characteristics, bleeding risk, tumor characteristics, extent of LNs dissection and reconstruction method.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, the estimated blood loss in the two groups was statistically different, but clinically not much different. Most of the existing studies comparing RPLG with FP-LDG have shown a similar result regarding the amount of estimated blood loss, prompting the conclusion that RPLG is as safe as FP-LDG [15,17,20,21]. As with the cause of difference in the operative time between the two groups, difference in the estimated blood loss might be understood.…”
Section: Discussionmentioning
confidence: 90%
“…Predictive parameter may be the number of retrieved lymph nodes. In addition, that of previous reports was 36.5 (range, , which seemed to be comparable with that of CLG (7,11,14,17,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The long-term results can be expected.…”
Section: Oncological Validitysupporting
confidence: 85%
“…The term RPLG can be applied to various procedures with various efforts to achieve minimal invasiveness. Many literatures indicated that RPLG procedures are comparable with CLG procedures (11,(35)(36)(37)(38)(39)(40)(41). The present authors' concept of RPLG was derived from SILG.…”
Section: Reduced-port Laparoscopic Gastrectomymentioning
confidence: 87%
See 1 more Smart Citation